Inactivation of SARS-CoV-2 by a chitosan/α-Ag2WO4 composite generated by femtosecond laser irradiation - Pereira, Paula Fabiana Santos; de Paula e Silva, Ana Carolina Alves [UNESP]; da Silva Pimentel, Bruna Natália Alves [UNESP]; Pinatti, Ivo Mateus [UNESP]; Simões, Alexandre Zirpoli [UNESP]; Vergani, Carlos Eduardo [UNESP]; Barreto-Vieira, Débora Ferreira; da Silva, Marcos Alexandre Nunes; Miranda, Milene Dias; Monteiro, Maria Eduarda Santos; Tucci, Amanda; Doñate-Buendía, Carlos; et al. (Springer Nature, 2022)
In the current COVID-19 pandemic, the next generation of innovative materials with enhanced anti-SARS-CoV-2 activity is urgently needed to prevent the spread of this virus within the community. Herein, we report the synthesis of chitosan/α-Ag2WO4 composites synthetized by femtosecond laser irradiation. The antimicrobial activity against Escherichia coli, Methicilin-susceptible Staphylococcus aureus (MSSA), and Candida albicans was determined by estimating the minimum inhibitory concentration (MIC) and minimal bactericidal/fungicidal concentration (MBC/MFC). To assess the biocompatibility of chitosan/α-Ag2WO4 composites in a range involving MIC and MBC/MFC on keratinocytes cells (NOK-si), an alamarBlue™ assay and an MTT assay were carried out. The SARS-CoV-2 virucidal effects was analyzed in Vero E6 cells through viral titer quantified in cell culture supernatant by PFU/mL assay. Our results showed a very similar antimicrobial activity of chitosan/α-Ag2WO4 3.3 and 6.6, with the last one demonstrating a slightly better action against MSSA. The chitosan/α-Ag2WO4 9.9 showed a wide range of antimicrobial activity (0.49–31.25 µg/mL). The cytotoxicity outcomes by alamarBlue™ revealed that the concentrations of interest (MIC and MBC/MFC) were considered non-cytotoxic to all composites after 72 h of exposure. The Chitosan/α-Ag2WO4 (CS6.6/α-Ag2WO4) composite reduced the SARS-CoV-2 viral titer quantification up to 80% of the controls. Then, our results suggest that these composites are highly efficient materials to kill bacteria (Escherichia coli, Methicillin-susceptible Staphylococcus aureus, and the yeast strain Candida albicans), in addition to inactivating SARS-CoV-2 by contact, through ROS production.